Choosing home : deciding to homeschool with Asperger's syndrome - Hartnett, Martha Kennedy, 1951- (J. Kingsley Publishers, 2004)
Martha Kennedy Hartnett is the mother of a child with Asperger's Syndrome who made the courageous choice to homeschool. Emerging from the author's personal experience, this book is a step by step account of successful home education. Choosing Home will take you into the homes of Asperger families as they journey from survival of the playground bully to making it work at home. Hartnett embraces those pertinent questions raised by parents: Will I be limiting my child's emotional and social development? How will I know if my teaching is good enough? What if I can't cope? These questions and many.
Keywords: Autistic children -- Education.; Home schooling.; Asperger's syndrome.; Asperger Syndrome; Enfants autistes -- Éducation.; Syndrome d'Asperger.; École à la maison.; EDUCATION -- Home Schooling.; Asperger's syndrome; Autistic children -- Education; Home schooling